Analysis of Metastatic Regional Lymph Node Locations and Predictors of Para-aortic Lymph Node Involvement in Endometrial Cancer Patients at Risk for Lymphatic Dissemination. Issue 4 (May 2015) - Altay, Ayse; Toptas, Tayfun; Dogan, Selen; Simsek, Tayup; Pestereli, Elif
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to provide detailed knowledge of the metastatic lymph node (LN) locations and to determine factors predicting para-aortic LN metastasis in endometrial cancer patients at risk (intermediate/high) for LN involvement. Methods A prospective case series with planned data collection was conducted in a total of 173 patients who treated with systematic pelvic para-aortic lymphadenectomy up to the renal vessels. All the LNs removed from pelvic and para-aortic basins—low or high according to the level of the inferior mesenteric artery—were evaluated separately. Logistic regression analyses were performed to determine the impact of variables on para-aortic metastasis. Results Lymph node metastasis was observed in 21.9% of the patients, pelvic LN involvement in 17.9%, para-aortic LN involvement in 15.0%, both pelvic and para-aortic LN involvement in 10.9%, and isolated para-aortic LN involvement in 4.0%. The most common metastatic LN locations were the external iliac (50.0%), obturator (50.0%), and low precaval regions (36.8%). The least common location of metastasis was the high precaval region (5.3%). Among patients with para-aortic LN metastasis, 42.3% had metastasis above the inferior mesenteric artery. The number of metastatic pelvic LNs greater than or equal to 2 was the only independent predictor of para-aortic metastasis in multivariate analysis (odds ratio, 23.38; 95% confidence interval, 1.35-403.99; P = 0.030), with 96.94% sensitivity, 95.87% specificity, 98.6% positive predictive value, and 97.0% negative predictive value. Conclusions The current study supports the idea that in patients at risk of LN involvement, the systematic lymphadenectomy should be performed up to the renal vessels due to the high rate of upper level involvement.